Migration of copper species in CexCu1−xO2 catalyst driven by thermal treatment and the effect on CO oxidation. Issue 32 (7th August 2017) - Xiong, Yan; Li, Lulu; Zhang, Lei; Cao, Yuan; Yu, Shuohan; Tang, Changjin; Dong, Lin
Abstract : A Cu-doped CeO2 solid solution was constructed by co-precipitation and additional acid treatment to investigate the behavior of doped copper under thermal treatment. Abstract : A Cu-doped CeO2 solid solution was constructed by co-precipitation and additional acid treatment to investigate the behavior of doped copper under thermal treatment. Acid treatment was used to intentionally remove the surface Cu species. Surface properties and fundamental characteristics of the catalysts were characterized by several techniques, as well as the CO oxidation performance. The results reveal that doped Cu ions could gradually migrate from the matrix to the catalyst surface during calcination. The degree of migration was mostly dependent on the calcination temperature, and also the concentration gradient of Cu between the surface and matrix. Catalytic testing in CO oxidation showed that the migration induced a distinct promotional effect on the activities of catalysts, supposedly closely related to the increased surface active Cu species and improved redox properties generated by the Cu migration. The present study offers renewed understanding of the dynamic behavior of ceria-based solid solution catalysts.